A Systematic Review of Holistic Care Management of Patients with Diabetes Mellitus - Suniyadewi, Ni Wayan; Kusnanto, Kusnanto; Juanamasta, I Gede; Rismayanti, I Dewa Ayu (International Journal of Psychosocial Rehabilitation, 2020)
Holistic care includes the bio-psycho-social and spiritual care of individuals. The purpose of this study is to explain the management of holistic care in people with diabetes mellitus. The study was done through a systematic review with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) approach. The search for articles included several databases: Ovid, CINAHL, and PubMed. Determination of keywords was based on PICOT framework, P: any diabetes population, I: holistic care, C: any comparison, O: blood sugar, T: any time. We used MeSH as a keyword. The inclusion criteria in this study were articles written in English, search from journals, articles available in full text, and original articles. Searching in journals is done by using the keywords holistic, diabetes mellitus and blood sugar. There were 10 journals reviewed. The result showed that explained holistic care is related to technology, holistic care program and holistic care related to complementary alternative medicine. The conclusion of this study is that holistic care programs provide significant results in the management of care for people with diabetes mellitus.